Atorvastatin reduces thrombin generation and expression of tissue factor, P-selectin and GPIIIa on platelet-derived microparticles in patients with peripheral arterial occlusive disease - Mobarrez, Fariborz; He, Shu; Bröijersen, Anders; Wiklund, Björn; Antovic, Aleksandra; Antovic, Jovan; Egberg, Nils; Jörneskog, Gun; Wallén, Håkan (Thrombosis and Haemostasis, 2011)
We investigated the effects of statin treatment on platelet-derived microparticles (PMPs) and thrombin generation in atherothrombotic disease. Nineteen patients with peripheral arterial occlusive disease were randomised to eight weeks of treatment with atorvastatin or placebo in a cross-over fashion. Expression of GPIIIa (CD61), P-selectin (CD62P), tissue factor (TF, CD142) and phosphatidylserine (PS; annexin-V or lactadherin binding) was assessed on PMPs. Thrombin generation in vivo was assessed by measurement of prothrombin fragment 1+2 in plasma (F1+2) and ex vivo by using the calibrated automated thrombogram (CAT). During atorvastatin treatment, expression of TF, P-selectin and GPIIIa was significantly reduced vs. placebo (p<0.001 for all). No effect on annexin-V or lactadherin binding was seen. Thrombin generation was significantly reduced during atorvastatin as assessed by both the CAT assay (p<0.001) and by measurements of F1+2 (p<0.01). Subsequent in vitro experiments showed that when TF on microparticles (MPs) was blocked by antibodies, the initiation of thrombin generation was slightly but significantly delayed. Blocking PS on MPs using annexin-V or lactadherin resulted in almost complete inhibition of thrombin generation. In conclusion, atorvastatin reduces thrombin generation and expression of TF, GPIIIa and P-selectin on PMPs in patients with peripheral vascular disease. Microparticle-bound TF slightly enhances initiation of thrombin generation whereas negatively charged surfaces provided by MPs or lipoproteins could reinforce thrombin generation. Statins may inhibit initiation of thrombin generation partly through a microparticle dependent mechanism but the main effect is probably through reduction of lipoprotein levels.
Keywords: Atorvastatin; peripheral arterial occlusive disease; platelet-derived microparticles; thrombin generation; tissue factor